Evaluation the Strategic Financial Performance of Commercial banks Field Study of Sample of Commercial Banks Operating in Sulaymaniyah Governorate - Rafhat Ghafar, Safin; dnan Khzer, Karzan A; Jebar Aziz, Nigar (Halabja University Journal, 2020)
The study dealt with the subject of strategic financial performance of a group of private banks operating in the province of Sulaymaniyah, where a set of financial indicators were chosen to evaluate the performance of these banks. The research sample also showed that the results of the analysis showed that the dijlah and furat Bank was distinguished in the overall performance indicators from the rest of the banks, and this reflects the administration’s success in this. The bank is planning and organizing in the direction of reaching a distinguished position. As was done through the analysis, a set of conclusions were reached that can be presented and based on these conclusions some recommendations can be presented that are expected to benefit the management of these banks in guiding them in increasing their efficiency and effectiveness to achieve their strategic objectives.